Konstruksi Hubungan Alam dan Manusia melalui Kerangka Maskulinitas Ekologis dalam Film Jungle (2017): Ekokritik Sastra - Nuril Rinahayu; Bayu Kristianto (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study examines the construction of the human-nature relationship in the Jungle (2017) movie. Jungle movie presents the mindset and behavior of men through four male characters (Yossi, Marcus, Kevin, and Karl) towards the wild (wilderness) as a masculinity framework. Using a qualitative method with an ecocriticism approach, especially related to ecological masculinity by Hultman and Pulé, this study shows how the construction of human-nature relationships through masculinity framework presents ecological masculinity as a form of hegemonic masculinity negotiation. The analysis focuses on two aspects of film studies: narrative and cinematographic by Bogss and Petrie. The results of this study indicate that in the depiction of nature through the Amazon Forest, nature is positioned as something dangerous, wild, scary, and capable of killing humans. Therefore, nature is represented as an entity that dominates humans. However, men's mindset and behavior towards nature present the illusion of a human versus nature dichotomy; in this case, the Jungle movie tries to present a critique of anthropocentrism. In addition, the mindset and behavior of male characters toward nature represent male masculinity models, especially ecological masculinity, as an alternative to hegemonic masculinity.